2016
DOI: 10.1093/europace/euw021
|View full text |Cite
|
Sign up to set email alerts
|

Automatic management of atrial and ventricular stimulation in a contemporary unselected population of pacemaker recipients: the ESSENTIAL Registry

Abstract: These algorithms for automatic management of pacing output ensure patient safety in the event of a huge increase of pacing threshold, while enabling maximization of battery longevity. Their applicability is quite broad in an unselected pacemaker population irrespectively of lead choice and service of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…Although some discrepancy may be observed between projections and real longevities, yet projections suited the “what‐if” purpose of our analysis providing estimations of future expected replacements, given the reported service times. Nevertheless longevity projections in the study devices has been proven sufficiently reliable at least in the 1‐year term as 1‐month projections fairly well predicted 12‐month projections …”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although some discrepancy may be observed between projections and real longevities, yet projections suited the “what‐if” purpose of our analysis providing estimations of future expected replacements, given the reported service times. Nevertheless longevity projections in the study devices has been proven sufficiently reliable at least in the 1‐year term as 1‐month projections fairly well predicted 12‐month projections …”
Section: Discussionmentioning
confidence: 79%
“…In the cohort considered here 153 months were technically achievable with current battery technology and outputs optimized to reduce energy consumption, but at full diagnostic capabilities. In the ESSENTIAL study the 93%‐97% reliability of the ACC function for managing pacing output may have significantly contributed to minimization of energy drain . Although such longevity values are still not ideal and there is room for improvement, our projections showed that further increase of device service life are expected to have less effect on future replacement rate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With another autocapture system of Biotronik pacemaker, Biffi et al . [9] demonstrated a significant increase of longevity using automatic atrial and ventricular amplitude adjustment versus fixed-output pacing during long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic verification of capture and output management were a breakthrough innovation brought in clinical practice 25 years ago, that lead to increased patient safety and pacemaker (PM) longevity, with greater benefit at high pacing thresholds . Nowadays, these algorithms are available in PM and cardiac resynchronization therapy (CRT) devices, and have specificities in terms of beat‐to‐beat capture verification, evoked response (ER) detection vs conduction to another cardiac chamber, maximum capture threshold that can be managed by automated capture verification, possibility to work at different pulse widths or with differently manufactured leads in relation to their polarization (low vs high) .…”
mentioning
confidence: 99%